A A Correlative Study on Bone Marrow Angiogenesis with Bone Marrow Fibrosis and Splenomegaly - Kulandaivel, Anbu Lenin; Gunasekaran, Kumudhini Priya (Annals of Pathology and Laboratory Medicine, 2018)
Background: Myelofibrosis is characterised by increased deposition of collagen type I and III in the bone marrow. Fibroplasia is associated with increased blood flow through marrow substance. Fibrosis occurs in variety of haematological and non haematological disorders. The present study was conducted to study the pattern of mean vessel density in various pathological disorders presenting with marrow fibrosis and to correlate it with spleen size. Methods: This is one year observational study undertaken in Department of pathology, Coimbatore medical college hospital, Coimbatore. A total of 25 cases presented with bone marrow fibrosis were taken and correlative study was done with mean vessel density and splenomegaly. Result: Of a total 25 Patients, 17 were secondary myelofibrosis and 8were Primary myelofibrosis. Patient from 18 to 80years were encountered in the study. Total of 13males and 12 females were included. Among Primary myelofibrosis 6 were males and 2 were females. Most of the cases of secondary myelofibrosis (11 out of 18) were Hematological malignancies which included AML(3), CML(2), CLL(1), MDS(1), NHL(3), MM(1).CD34 Immunostaining showed increased mean vessel density among all the cases of primary myelofibrosis. Conclusion: Reticulin fibrosis occurs in variety of Hematological, Non Hematological Malignancies and Non neoplastic disorders including Tuberculosis, SLE and post radiotherapy accompanied by various degree of mean vessel density. Increase in MVD is considered as mother event in causing fibrosis and splenomegaly. Hence studying MVD and correlating it with fibrosis and splenomegaly will be helpful in evaluating the disease progression.